The anti-inflammatory mechanism of SAHA in acute pancreatitis through HDAC5/SLIT2/Akt/β-catenin axis. Issue 12 (12th January 2022) - Tong, Jinxue; Zhou, Jiandang; Fang, Min; Wang, Gang; Fu, Songbin; Sun, Bei; Lv, Jiachen
Abstract: Acute pancreatitis (AP) is widely recognized to be an inflammation-related disease, in which HDAC was upregulated. The anti-inflammatory role of suberoylanilide hydroxamic acid (SAHA), a HDAC inhibitor, has been documented. In this context, this research was implemented to figure out whether SAHA manipulated inflammation in AP. Subsequent to induction of AP mouse model, HDAC5 expression was detected. The binding of HDAC5 and SLIT2 was detected by Co-Immunoprecipitation and Chromatin immunoprecipitation assays. SAHA treatment and gain- and loss-of-function approaches were used in AP mice and lipopolysaccharide (LPS)-induced pancreatic acinar cells. In mice, biochemical methods were implemented to measure activities of pancreatic lipase, trypsin, myeloperoxidase (MPO) and pancreatic edema, TUNEL staining to determine pancreatic cell apoptosis, and flow cytometry to assess the total number of leukocytes and neutrophils in pancreas. In pancreatic acinar cells, CCK-8 was performed to evaluate cell viability. HDAC5 exhibited overexpression in AP mice. Mechanical analysis showed that HDAC5 facilitated SLIT2 deacetylation to downregulate SLIT2, thus activating Akt/β-catenin pathway in pancreatic acinar cells. SAHA treatment, HDAC5 silencing or SLIT2 overexpression diminished inflammation in AP in vivo and in vitro . SAHA treatment, HDAC5 silencing or SLIT2 overexpression reduced activities of pancreatic lipase, trypsin, MPO, pancreatic edema and cell apoptosis in AP mice as well as elevated viability of LPS-induced pancreatic acinar cells. SAHA might exert anti-inflammatory effects in AP mice via HDAC5/SLIT2/Akt/β-catenin axis.